American-type options. - Silʹvestrov, D. S. (Dmitriĭ Sergeevich) (De Gruyter studies in mathematics ;, 2015)
The second volume of this systematical presentation of stochastic approximation methods for models of American-type options presents results on structural studies of optimal stopping domains, Monte Carlo based approximation reward algorithms, and convergence of American-type options for autoregressive and continuous time models, as well as results of the corresponding experimental studies.